Investigating the Relationships Between Cultural Embeddedness, Happiness, and Knowledge Management Practices in an Inter-Organizational Virtual Team - Chumg, Hao-Fan; Huang, Chao-Jung (Frontiers in Psychology, 2021)
In light of the considerable disparity in the thinking patterns between Western and Chinese societies, this study seeks to develop a better comprehension of the influences of traditional Chinese cultural elements on knowledge management (KM) practices within contemporary Taiwanese society. To this end, the research draws on the concepts of “guanxi” based on the embeddedness theory concept through the lens of employees’ happiness. A qualitative case study was conducted within a virtual team (in this case, Taiwanese Farmers’ Associations (FAs)), and data were collected from both observations and 36 interviewees. Based on the resulting analysis, the findings show that individuals’ knowledge-sharing behavior results from a complex interplay of a sense of well-being, guanxi, and the Chinese culture rooted within such organizations. The study provides a significant insight into the cultural implications of KM strategies and offers valuable advice for knowledge managers within the context of Taiwanese society.